Regulatory approach for dilute and disperse or concentrate and store of the patient's excreta after iodine therapy - Mustafa Majali; Buthaina Al Ameri (Open Journal of Thyroid Research - Peertechz Publications, 2022)
This study is intended to provide for decision-makers simple criteria for determining which option or approach either dilute and disperse or concentrate and store of the Patient's Excreta after Iodine therapy would be identical to the exemption criteria, the radiation risk is sufficiently low as not to warrant any further control and has no regulatory concern. Additionally, ensure that the selected option would be inherently safe, with no appreciable likelihood of scenarios that could lead to a failure to meet both no concern and no regulatory control.